Measurement of Soil Parameters Using Sensor Network - et al., G. Joselin Retna Kumar (International Journal of Advanced Science and Technology, 2020)
Plants mainly utilize the macronutrients Nitrogen, Phosphorus and Potassium (in short as NPK) in the soil. The soil fertility and the root growth in plants are dependent on the nutrient levels in the soil. After annual seasonal harvest, the nutrient level in soil gets depleted, in order to replenish these nutrients fertilizers are recommended based on soil tests. Modern day, farmers and plantation workers require easily available, robust, ready-made instrumental devices to measure the nutrients in the soil. Our task recommendation is to develop an IoT logical measuring device which can be used to remotely monitor and estimate the soil macronutrient levels using sensor network. The nutrient concentration is estimated using statistical data analysis and the values obtained are normalized based on soil conditions. We are operating the system with a TI Microcontroller to control and transmit information. A sensor network is interfaced to draw sample readings from the soil. For our project we are making use of capacitive type soil moisture sensor in order to obtain the soil measurable. The data gathered are recorded and displayed on a developed mobile application. Our system provides the following soil parameters: - soil moisture, electrical conductivity and Macronutrient (Nitrogen, phosphorus and Potash) levels in the soil. On analysis of the data gathered, the deficient supplements in the soil is found and the fertilizer required to compensate the depleted nutrients can be estimated. We develop this system for the benefit of farmers and plantation workers to test and monitor the soil parameters of their field.